EEG(brain-wave) for gaming using Emotiv Insight - Ng, Ming Sheng (Nanyang Technological University, 2022)
Technology has improved people's quality of life since the use of modern tools allows industrialists to produce better and higher quality products. Nowadays, several AI algorithms such as machine learning or deep learning are being applied as a tool to solve problems or to make predictions in many different areas.